Treatment approaches and outcomes of major chest wall resections and reconstructions in patients with soft tissue and bone sarcomas: a retrospective observational study - Ozaniak, Andrej; Galova, Dominika; Benesova, Iva; Lischke, Robert; Ozaniak Strizova, Zuzana (Journal of thoracic disease, 2024)
BACKGROUND: Chest wall sarcomas are rare and pose significant technical challenges in surgical management, particularly in patients with advanced disease. In this study, we examined the extent of resection, reconstruction techniques, and oncological outcomes of patients with chest wall soft tissue and bone sarcomas. METHODS: This retrospective single-center series included patients who underwent surgery at our center between May 2014 and February 2022 for deep-seated/subfascial primary and recurrent soft tissue or bone sarcomas of the chest wall requiring significant resection and extensive reconstruction. We analyzed clinical and operative data, including extent of resection, reconstruction techniques, and oncological outcomes. Additionally, we compared survival outcomes between patients with primary and recurrent tumors, and examined how these were influenced by clinical factors using Cox proportional hazards regression analysis. RESULTS: Of the 38 patients included, 22 were treated for primary or recurrent soft tissue sarcoma (STS) and 16 for bone sarcoma. En bloc microscopic radical resection (R0) was achieved in 95.45% and 93.75% of patients with soft tissue and bone sarcomas, respectively. Nonetheless, local recurrence or distant metastases occurred in 40%, 58.33%, and 40% of patients with primary soft tissue, recurrent soft tissue, and bone sarcomas, respectively. Adherence to clinical guidelines and treatment in the reference center was high for bone sarcoma (93.75%), but notably low for STS, resulting in 54.55% of these patients requiring re-resection. Compared with those who underwent only one surgery, patients who underwent re-resection had poorer postoperative outcomes, more severe complications, and longer hospital stay. CONCLUSIONS: Chest wall sarcomas often require extensive resection and complex reconstruction. Although surgical treatment at reference sarcoma centers has significantly improved oncological and clinical outcomes, the prognosis of these patients remains guarded, necessitating further related research and continued refinement in surgical techniques, adjuvant therapies, and follow-up strategies.